Physicochemical characteristics of blackberry (iRubus glaucus /i Benth.) fruits from four production zones of Cundinamarca, Colombia (2016)
Blackberries play an important role in human nutrition, due to the elevated content of certain bioactive compounds including ascorbate, anthocyanins, phenolic acids, carbohydrates, and proteins. Blackberry Rubus glaucus from Colombian Andes has a high demand on regional and international markets and there is much interest in its cultivation to increase the commercial offer. In four blackberry producing municipalities of Cundinamarca province, fruits were harvested for different quality tests based on the availability of hydric resources in the zone and their influence on fruit characteristics according to the precipitation of each zone, since the crops did not have an irrigation system. The variables, such as size, fresh weight, texture, pH, titratable total acids (TTA), total soluble solids (TSS), and color were evaluated to compare the quality of the fruits between the municipalities, finding that fruits from Silvania had the greater size but, in turn, were the least consistent. El Colegio zone presented the sweetest fruits and together with Pasca had the highest acidity percentage. The color of Pasca and Silvania fruits was the most attractive for commercialization parameters. These parameters, even when management and agro-climatic conditions between municipalities were very similar, allows knowing the positive attributes and determine the factors that need to be improved and to project on a shortterm future productions acceptable on the international market